2010
DOI: 10.1519/jsc.0b013e3181c643a0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warming-up on Physical Performance: A Systematic Review With Meta-analysis

Abstract: The value of warming-up is a worthy research problem because it is not known whether warming-up benefits, harms, or has no effect on individuals. The purpose of this study was to review the evidence relating to performance improvement using a warm-up. A systematic review and meta-analysis were undertaken. Relevant studies were identified by searching Medline, SPORTDiscus, and PubMed (1966-April 2008). Studies investigating the effects of warming-up on performance improvement in physical activities were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
194
0
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(224 citation statements)
references
References 17 publications
7
194
0
23
Order By: Relevance
“…Warm-up is generally performed previously to exercise to increase performance, however the literature has shown in most studies that warm-up does not change 1,2 . We have previously shown that warm-up did not influence performance on different exercise protocols 14.15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Warm-up is generally performed previously to exercise to increase performance, however the literature has shown in most studies that warm-up does not change 1,2 . We have previously shown that warm-up did not influence performance on different exercise protocols 14.15 .…”
Section: Discussionmentioning
confidence: 99%
“…Warm-up is defined as a "protocol specifically undertaken to prepare for the onset of subsequent physical activity", however the effect of different methods of warm-up are unclear 1 , and coaches often base their warmup sessions on empiric observations rather than scientific studies 2 . The most commonly used warm-ups in sports are composed of low intensity aerobic activity, muscle stretching and sport-specific movements 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…by Kris Smith, OTR-L S tretching has long been advocated by physical and occupational therapists as a way to improve flexibility and decrease risk of injury to shoulders, back, hips, and knees (Fradkin, Zazryn, & Smoliga, 2010). Tight muscles have been linked to back pain and shoulder injury by affecting the viscoelastic changes in the muscle-tendon unit (da Costa & Vieira, 2008).…”
Section: Evaluation Of a Stretching Program To Increase Worker Flexibmentioning
confidence: 99%